PENGARUH TINDAKAN SUPERVISI DAN EXTERNAL LOCUS OF CONTROL TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT PADA AUDITOR DI SURABAYA - Kristanti, Natalia; Lasdi, Lodovicus (Jurnal Akuntansi Kontemporer, 2016)
Premature termination on the audit procedures is the action taken by the auditor does not perform or ignore one or several audit procedures are required, but the auditor to document all audit procedures have been completed appropriately. Factors affect-ing this action one of them is an act of supervision and external locus of control. This study aims to examine the effect of supervi-sion measures and external locus of control on top of premature termination of audit procedures. The object of this study is the auditor in KAP Surabaya with sample 57 respondents to the survey method. The sampling technique in this research is conven-ience sampling. Data were analyzed using multiple linear regression. The results showed that the act of supervision significant negative effect on premature termination of audit procedures. External locus of control is a significant positive against premature termination on the audit procedures.